Land cover changes in protected areas of Slovakia between 1990 and 2018 - Michaela Žoncová (Acta Geographica Slovenica, 2020)
As a country with abundant natural resources, Slovakia has legislation to protect significant parts of nature and landscape. The paper aimed to identify the extent and nature of land cover changes in large protected areas in Slovakia and to determine how had these changes impacted the diversity and ecological stability of the landscape. We used the CORINE Land Cover data from 1990 and 2018 to identify landscape changes and analyzed them spatially and statistically. Overall, 21.7% of the total area was changed. In terms of landscape changes, nine dominant sub-processes within five »land cover flows« were identified. In terms of changes in landscape diversity and stability the most significant changes occurred in the NP Nízke Tatry.